An IFN-STAT Axis Augments Tissue Damage and Inflammation in a Mouse Model of Crohn's Disease - Stolzer, Iris; Dressel, Anja; Neurath, Markus; Günther, Claudia; Chiriac, Mircea-Teodor (Frontiers in Medicine, 2021)
Blocking interferon-function by therapeutic intervention of the JAK-STAT-axis is a novel promising treatment option for inflammatory bowel disease (IBD). Although JAK inhibitors have proven efficacy in patients with active ulcerative colitis (UC), they failed to induce clinical remission in patients with Crohn's disease (CD). This finding strongly implicates a differential contribution of JAK signaling in both entities. Here, we dissected the contribution of different STAT members downstream of JAK to inflammation and barrier dysfunction in a mouse model of Crohn's disease like ileitis and colitis (Casp8ΔIEC mice). Deletion of STAT1 in Casp8ΔIEC mice was associated with reduced cell death and a partial rescue of Paneth cell function in the small intestine. Likewise, organoids derived from the small intestine of these mice were less sensitive to cell death triggered by IBD-key cytokines such as TNFα or IFNs. Further functional in vitro and in vivo analyses revealed the impairment of MLKL-mediated necrosis as a result of deficient STAT1 function, which was in turn associated with improved cell survival. However, a decrease in inflammatory cell death was still associated with mild inflammation in the small intestine. The impact of STAT1 signaling on gastrointestinal inflammation dependent on the localization of inflammation, as STAT1 is essential for intestinal epithelial cell death regulation in the small intestine, whereas it is not the key factor for intestinal epithelial cell death in the context of colitis. Of note, additional deletion of STAT2 was not sufficient to restore Paneth cell function but strongly ameliorated ileitis. In summary, we provide here compelling molecular evidence that STAT1 and STAT2, both contribute to intestinal homeostasis, but have non-redundant functions. Our results further demonstrate that STATs individually affect the distinct pathophysiology of inflammation in the ileum and colon, respectively, which might explain the diverse outcome of JAK inhibitors on inflammatory bowel diseases.
CRIS-Team Scopus Importer:2021-06-25
Keywords: cell death; inflammation; inflammatory bowel disease; Paneth cells; STAT signaling

IL-20 controls resolution of experimental colitis by regulating epithelial IFN/STAT2 signalling - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Günther, Claudia; Gonzalez Acera, Miguel; Atreya, Raja; Stolzer, Iris; Wittner, Leonie; Dressel, Anja; Schickedanz, Laura; Gámez Belmonte, Maria de los Reyes; Erkert, Lena; Hundorfean, Gheorghe; et al. (Gut, 2023)
Objective: We sought to investigate the role of interleukin (IL)-20 in IBD and experimental colitis. Design: Experimental colitis was induced in mice deficient in components of the IL-20 and signal transducer and activator of transcription (STAT)2 signalling pathways. In vivo imaging, high-resolution mini-endoscopy and histology were used to assess intestinal inflammation. We further used RNA-sequencing (RNA-Seq), RNAScope and Gene Ontology analysis, western blot analysis and co-immunoprecipitation, confocal microscopy and intestinal epithelial cell (IEC)-derived three-dimensional organoids to investigate the underlying molecular mechanisms. Results were validated using samples from patients with IBD and non-IBD control subjects by a combination of RNA-Seq, organoids and immunostainings. Results: In IBD, IL20 levels were induced during remission and were significantly higher in antitumour necrosis factor responders versus non-responders. IL-20RA and IL-20RB were present on IECs from patients with IBD and IL-20-induced STAT3 and suppressed interferon (IFN)-STAT2 signalling in these cells. In IBD, experimental dextran sulfate sodium (DSS)-induced colitis and mucosal healing, IECs were the main producers of IL-20. Compared with wildtype controls, Il20-/-, Il20ra-/- and Il20rb-/- mice were more susceptible to experimental DSS-induced colitis. IL-20 deficiency was associated with increased IFN/STAT2 activity in mice and IFN/STAT2-induced necroptotic cell death in IEC-derived organoids could be markedly blocked by IL-20. Moreover, newly generated Stat2ΔIEC mice, lacking STAT2 in IECs, were less susceptible to experimental colitis compared with wildtype controls and the administration of IL-20 suppressed colitis activity in wildtype animals. Conclusion: IL-20 controls colitis and mucosal healing by interfering with the IFN/STAT2 death signalling pathway in IECs. These results indicate new directions for suppressing gut inflammation by modulating IL-20-controlled STAT2 signals.
CRIS-Team Scopus Importer:2023-11-17
Keywords: experimental colitis; inflammatory bowel disease; interferon; interleukins; signal transduction

Visualizing transfer of microbial biomolecules by outer membrane vesicles in microbe-host-communication in vivo - Bittel, Miriam; Reichert, Patrick; Sarfati, Ilann; Dressel, Anja; Leikam, Stefanie; Uderhardt, Stefan; Stolzer, Iris; Phu, Tuan Anh; Ng, Martin; Vu, Ngan K.; Tenzer, Stefan; Distler, Ute; et al. (Journal of Extracellular Vesicles, 2021)
The intestinal microbiota influences mammalian host physiology in health and disease locally in the gut but also in organs devoid of direct contact with bacteria such as the liver and brain. Extracellular vesicles (EVs) or outer membrane vesicles (OMVs) released by microbes are increasingly recognized for their potential role as biological shuttle systems for inter-kingdom communication. However, physiologically relevant evidence for the transfer of functional biomolecules from the intestinal microbiota to individual host cells by OMVs in vivo is scarce. By introducing Escherichia coli engineered to express Cre-recombinase (E. coliCre) into mice with a Rosa26.tdTomato-reporter background, we leveraged the Cre-LoxP system to report the transfer of bacterial OMVs to recipient cells in vivo. Colonizing the intestine of these mice with E. coliCre, resulted in Cre-recombinase induced fluorescent reporter gene-expression in cells along the intestinal epithelium, including intestinal stem cells as well as mucosal immune cells such as macrophages. Furthermore, even far beyond the gut, bacterial-derived Cre induced extended marker gene expression in a wide range of host tissues, including the heart, liver, kidney, spleen, and brain. Together, our findings provide a method and proof of principle that OMVs can serve as a biological shuttle system for the horizontal transfer of functional biomolecules between bacteria and mammalian host cells.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Cre-Loxp; extracellular vesicles; inflammation; intestinal stem cells; microbiome; outer membrane vesicles